Autophagy regulates TNFα-mediated joint destruction in experimental arthritis. Issue 5 (12th September 2012) - Lin, Neng-Yu; Beyer, Christian; Gießl, Andreas; Kireva, Trayana; Scholtysek, Carina; Uderhardt, Stefan; Munoz, Luis Enrique; Dees, Clara; Distler, Alfiya; Wirtz, Stefan; Krönke, Gerhard; Spencer, Brian; et al.
Abstract : Objectives: Autophagy is a homeostatic process to recycle dispensable and damaged cell organelles. Dysregulation of autophagic pathways has recently been implicated in the pathogenesis of various diseases. Here, we investigated the role of autophagy during joint destruction in arthritis. Methods: Autophagy in osteoclasts was analysed in vitro and ex vivo by transmission electron microscopy, Western blotting and immunohistochemistry for Beclin1 and Atg7. Small molecule inhibitors, LysMCre-mediated knockout of Atg7 and lentiviral overexpression of Beclin1 were used to modulate autophagy in vitro and in vivo. Osteoclast differentiation markers were quantified by real-time PCR. The extent of bone and cartilage destruction was analysed in human tumour necrosis factor α transgenic (hTNFα tg) mice after adoptive transfer with myeloid specific Atg7-deficient bone marrow. Results: Autophagy was activated in osteoclasts of human rheumatoid arthritis (RA) showing increased expression of Beclin1 and Atg7. TNFα potently induced the expression of autophagy-related genes and activated autophagy in vitro and in vivo. Activation of autophagy by overexpression of Beclin1-induced osteoclastogenesis and enhanced the resorptive capacity of cultured osteoclasts, whereas pharmacologic or genetic inactivation of autophagy prevented osteoclast differentiation. Arthritic hTNFα tg mice transplanted with Atg7 fl/fl ×LysMCre + bone marrow cells (BMC) showed reduced numbers of osteoclasts and were protected from TNFα-induced bone erosion, proteoglycan loss and chondrocyte death. Conclusions: These findings demonstrate that autophagy is activated in RA in a TNFα-dependent manner and regulates osteoclast differentiation and bone resorption. We thus provide evidence for a central role of autophagy in joint destruction in RA.